Effectiveness Of Beetroot And Spinach Against The Increase In Hemoglobin Levels Of Pregnant Women In The Primary Clinic Kasih Bunda, 2022 - Wahyu Istiqomah; Achmad Fauzi (STIKep PPNI Jawa Barat, 2022)
Aims: Pregnant women who suffer from anemia are at risk of miscarriage, premature birth, low birth weight babies, and bleeding before and after delivery. Purpose: It is known the effectiveness of giving beetroot and spinach to increase hemoglobin levels in pregnant women in primary clinics in 2022. Methods: One-group